TREN PERKEMBANGAN PENELITIAN AKUNTANSI HIJAU: SYSTEMATIC LITERATURE REVIEW - Paledung, Marannu; Nurdiyanti, Desi; Damayanti, Ratna Ayu; Said, Darwis (Jurnal Akuntansi Kontemporer, 2023)
Research Purposes: This study aims to review the information that has existed in previous studies because the concept of Green Accounting (GA) in Indonesia is still in the growth stage and as a basis for scientific development and can provide ideas related to new topics in the future. Research Methods: This research used the systematic literature review (SLR) method and a total of 47 articles accredited with SINTA was analyzed in this study.Research Results and Findings: The development trend of the number of publications related to Green Accounting is still fluctuating from 2012 to 2022. The most used research method is quantitative research. The most widely used instruments in collecting data in such studies mainly used documentation techniques. And analyze the most widely used data is the multiple regression method. The overall research series related to the implementation of GA in Indonesia is quite good but needs improvement because there has not been much research and limited topics. This research has implications for environmental management actions, and efforts based on environmentally friendly principles or green innovation can continue to increase.